Letting Go To Become Whole, Celebrating The Love-Sorrow Theopoetics Through the Mystical Path of Meister Eckhart in the Song “I Love You But I’m Letting Go” by Pamungkas - Josua Estomihi Butarbutar; August Corneles Tamawiwy (Litbang STFT Widya Sasana Malang, 2026)
This article explores the concept of radical letting go (Gelassenheit) as a path to self-wholeness, integrating the mysticism of Meister Eckhart and the theopoetics proposed by John D. Caputo, using the song